2018
DOI: 10.1016/j.psychsport.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The role, benefits and selection of sport psychology consultants: Perceptions of youth-sport coaches and parents

Abstract: Running Head: The role, benefits and selectionThe role, benefits and selection of sport psychology consultants: Perceptions of youth-sport coaches and parents Abstract 1 Objectives: With practitioners needing to be 'more things to more people', it is essential to 2 understand third-party consumer perceptions of the role and benefits of sport psychology 3 consultants (SPC), and the characteristics that may influence such services being sought. 4Design: A qualitative thematic analysis approach was used in Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Currently, sports psychology focuses on the analysis of diverse psychological variables and cognitive processes affecting the athletes’ performance, concentrating on improving their cognitive abilities with the intention of maximising efficiency. In this sense, it makes it necessary to study certain variables such as motivational climate, leadership, anxiety, emotional intelligence or resilience due to their great influence on athletes’ performance, making these factors a fundamental object of study for specialists in sports psychology [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, sports psychology focuses on the analysis of diverse psychological variables and cognitive processes affecting the athletes’ performance, concentrating on improving their cognitive abilities with the intention of maximising efficiency. In this sense, it makes it necessary to study certain variables such as motivational climate, leadership, anxiety, emotional intelligence or resilience due to their great influence on athletes’ performance, making these factors a fundamental object of study for specialists in sports psychology [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that psychological preparation strategies can be successfully utilized to combat negative emotional states often experienced by athletes as anxiety, and to prolong high levels of adherence and performance throughout the sporting season [2]. A better understanding of the predictors of anxiety, motivational climate, and mental health enables efficacious strategies to be designed for various sport modalities [2][3][4]. The influence of the specific characteristics of various types of sports (including their internal dynamics, ways of association, or forms of contact between rivals and peers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Currently, psychology of sports has become particularly relevant, focusing on analysing factors and psychological processes in athletes, during training sessions, precompetitive training or during the competition (Thelwell, Wood, Harwood, Woolway & Van Raalte, 2018).…”
Section: Introductionmentioning
confidence: 99%